Clinical Characteristics and Surgical Outcomes of Sinonasal Lesions Associated With Tumor-Induced Osteomalacia. (July 2021) - Zhu, Zhenzhen; Xia, Weibo; Qi, Fang; Wang, Weiqing; Wang, Xiaowei; Zha, Yang; Li, Fang; Jing, Hongli; Wang, Peipei; Lv, Wei
Objective: To investigate the clinical characteristics and surgical outcomes of sinonasal tumors associated with tumor-induced osteomalacia (TIO). Study Design: Retrospective case series. Setting: Single tertiary center. Methods: We studied the clinical characteristics and surgical outcomes of 43 patients (22 male, 21 female) who had lesions in the nasal cavity and paranasal sinus associated with TIO and underwent surgery between August 2006 and November 2019. Results: The mean ± SD duration between the onset of symptoms and surgery was 3.9 ± 2.6 years. The most common tumor site was the ethmoid sinus (76.7%), and the skull base was involved in 12 cases. Phosphaturic mesenchymal tumors were diagnosed in 41 patients, among whom there was 1 multifocal case. Another 2 cases involved odontogenic fibroma and hemangiofibroma, respectively. Serum phosphorus normalized in 39 cases within 4.4 ± 2.3 days, and serum fibroblastic growth factor 23 normalized within 1 day; clinical symptoms, however, gradually improved within several months after the first operation. There was no significant difference in the recovery rate between endoscopic and open surgery ( P = 0.639). Two patients with recurrent cases and 2 with nonremission cases recovered after a sinonasal reoperation. The patient with a multifocal case recovered after the resection of the tumors in the ethmoid sinus and mandible. The overall recovery rate was 97.7%. Conclusion: Most sinonasal tumors associated with TIO are located in the ethmoid sinus, and the skull base is involved in some cases. Complete excision of the tumor leads to recovery, and endoscopic surgery could achieve recovery rates similar to those of open surgery.